Evaluation of diet quality and its associated factors among adolescents in Kuala Lumpur, Malaysia - Rezali, Fara Wahida; Chin, Yit Siew; Mohd Shariff, Zalilah; Mohd Yusof, Barakatun Nisak; V. Sanker, Kaartina; Woon, Fui Chee (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2015)
BACKGROUND/OBJECTIVES: This study aims to determine contribution of meal frequency, self-efficacy for healthy eating, and availability of healthy foods towards diet quality of adolescents in Kuala Lumpur, Malaysia. SUBJECTS/METHODS: This study was conducted among 373 adolescents aged from 13 to 16 years old. Diet quality of the respondents was assessed using the Healthy Eating Index for Malaysians. Meal frequency, self-efficacy for healthy eating, and availability of healthy foods were assessed through the Eating Behaviours Questionnaire (EBQ), self-efficacy for healthy eating scale, and availability of healthy foods scale, respectively. RESULTS: The majority of the respondents (80.7%) were at risk of poor diet quality. Males (mean = 34.2 ± 8.2%) had poorer diet quality than females (mean = 39.9 ± 9.0%) (t = -5.941, P < 0.05). Malay respondents (mean = 36.9 ± 8.7%) had poorer diet quality than Indian respondents (mean = 41.3 ± 10.0%) (F = 2.762, P < 0.05). Age (r = 0.123, P < 0.05), self-efficacy for healthy eating (r = 0.129, P < 0.05), and availability of healthy foods (r = 0.159, P < 0.05) were positively correlated with the diet quality of the respondents. However, meal frequency was not correlated with the diet quality of the respondents. Multiple linear regression analysis showed that being a male, being a Malay, low self-efficacy for healthy eating, and low availability of healthy foods contributed significantly towards poor diet quality among respondents. CONCLUSIONS: In short, sex, ethnicity, self-efficacy for healthy eating, and availability of healthy foods were associated with diet quality among adolescents. Health practitioners should take into consideration of differences in sex and ethnicity during implementation of nutrition-related intervention programs. Self-efficacy for healthy eating and availability of healthy foods should be included as important components in improving diet quality of adolescents.